How to solve 3x-3 / X-2 + X-5 / X-8 = 3x-9 / x-4 + x-3 / X-6

How to solve 3x-3 / X-2 + X-5 / X-8 = 3x-9 / x-4 + x-3 / X-6

(3x-3)/(x-2)+(x-5)/(x-8)=(3x-9)/(x-4)+(x-3)/(x-6)
(3x-3)/(x-2)-(3x-9)/(x-4)=(x-3)/(x-6)-(x-5)/(x-8)
3[(x-1)/(x-2) -(x-3)/(x-4)]=(x-3)/(x-6)-(x-5)/(x-8)
Right and left at the same time
3[(x-1)(x-4)-(x-3)(x-2)]/(x-2)(x-4)=[(x-3)(x-8)-(x-5)(x-6)]/(x-6)(x-8)
3(x²-5x+4-x²+5x-6)/(x-2)(x-4) =(x²-11x+24-x²+11x-30)/(x-6)(x-8)
3×(-2)/(x-2)(x-4)=(-6)/(x-6)(x-8)
1/(x-2)(x-4)=1/(x-6)(x-8)
(x-2)(x-4)=(x-6)(x-8)
x²-6x+8=x²-14x+48
-6x+14x=48-8
8x=40
x=5